Analisis Implementasi Pengelolaan Alokasi Dana Desa (ADD) di Desa Maitara Kota Tidore Kepulauan - Muhammad Hi Hasan (Peneliti.net, 2020)
The objectives of this study were 1) To analyze the process of compiling and determining the village management plan (DD) in the village of Maitara, Tidore Islands City. 2) To analyze the effectiveness of village funds in village development and community empowerment in Maitara village, Tidore Islands City. 3) For Village Fund Management (DD) in Maitara Village, Tidore Islands City, has followed the Government Accounting Standards? Research subjects for government officials in the village and sub-district environment or community leaders and parties who understand / understand the Village Fund in the relevant area. The documentation method is used to obtain data in accordance with the actual situation (interpretive qualitative). The interview method by making a manuscript was used to obtain data on the management of village funds (DD).